Retroalimentación y trabajo en equipo en estudiantes universitarios de una universidad nacional de Lima Metropolitana - Abad-Lezama, Irene Roxana (2023)
Formative feedback must be reflected as a daily strategy in educational action. Therefore, the objective of the research was to determine the relationship between feedback and teamwork in university students of a national university in Metropolitan Lima. The positivist paradigm was followed, under the quantitative approach, non-experimental design and correlational type. The population and sample was defined by 146 university students from the different departments of the Faculty of Social Sciences and Humanities, who are enrolled in pre-professional practices corresponding to cycles V to X, at a public university in Lima, Peru. The technique was the survey and the questionnaire was used as an instrument. It is concluded that there is a significant relationship between feedback and teamwork in university students, contributing to the academic and professional training of students. Formative feedback must become a daily strategy that allows the educational actors involved in the process to learn to unlearn to build new knowledge, promoting teamwork under a systemic vision.